First isolation of Yersinia entomophaga in human urinary tract. (November 2018) - Le Guern, A.-S.; Savin, C.; Brémont, S.; Payro, G.; Bon, D.; Carniel, E.; Pizarro-Cerdá, J.
Abstract: Yersinia entomophaga is an insect pathogen first isolated from larvae of Coleoptera in New Zealand in 2011. We report here the first isolation of Y. entomophaga from human urine. Using whole-genome sequencing, we confirmed the presence of specific chromosomal virulence genes and identified a plasmid harbouring a quinolone resistance gene.